In-orbit micro-propulsion demonstrator for PICO-satellite applications. (December 2019) - Pallichadath, V.; Turmaine, L.; Melaika, A.; Gelmi, S.; Ramisa, M. Vilella; Rijlaarsdam, D.; Silva, M.A.C.; Guerrieri, D.C.; Uludag, M.S.; Zandbergen, B.; Cervone, A.
Abstract: Delft University of Technology is currently developing the pico-satellite platform Delfi-PQ, based on the PocketQube standard, in pursuit of a new generation of satellites with lower cost, flexibility and short development time. A technology demonstration payload expected to fly in one of the first Delfi-PQ satellites is a dual thruster micro-propulsion system based on the use of water as propellant. Two different micro-resistojet concepts will be demonstrated in the same satellite flight: one based on vaporization, heating and expansion in a nozzle of pressurized liquid water (Vaporizing Liquid Micro-resistojet); the other based on heating and acceleration in slots with simple geometry of molecules of vapour under transitional or free molecular flow regime (Low Pressure Micro-resistojet). The demonstrator is based on a common propellant storage for the two micro-propulsion concepts, based on the use of the capillarity properties of water in a small diameter tube connected to the two separate MEMS thruster chips with their own dedicated valves. This paper describes the requirements and design of the complete micro-propulsion demonstrator as well as its expected operational envelope for in-orbit functional testing, based on the currently validated performance characteristics of the two thrusters. Highlights: MEMS micro-propulsion is a promising way to enhance pico-satellites capabilities. Two Micro-resistojet propulsion methods are presented. Dual thruster demonstrator based on the use of water as propellant. Design and in-orbit demonstration including firing modes and phases are presented.